Emmanuel Alloa, „Rezistența sensibilului. Merleau-Ponty și critica transparenței”, Oradea: Ratio & Revelatio, 2025, ISBN 978-630-6657-23-0 - MÂNDRUȚ, David-Augustin (Studia Universitatis Babeș-Bolyai Philosophia, 2025)
The Romanian translation of Emmanuel Alloa’s book entitled the Resistance of the Sensible provides the reader with an overview of the key concepts of Merleau-Ponty’s developing thought. Not only does the author of the book touch upon several aspects that have been overlooked by the current exegesis, but he also provides a unitary view on Merleau-Ponty’s idea of transparency, as is found in the corpus of his work. Moreover, Alloa suggests some critical remarks concerning how Merleau-Ponty’s thought can be enriched by comparing it with research stemming from psychology, linguistics and the history of philosophy. For example, the last chapter of his book compares the thematization of Aristotle with the late thinking of Merleau-Ponty, to finally propose the notion of “diaphenomenology” as emblematic of the French phenomenologist’s thinking. Alloa commences with the simple, yet definitory question of what does perceptual evidence exactly mean? We can just think of Merleau-Ponty’s early magnum opus entitled the Phenomenology of Perception, wherein the French philosopher engages with the framework of Husserl, at the same time, advancing theories which have their origin in psychiatry or psychology. Perceptual evidence designates, first and foremost, the givenness of the object as something coherent, permanent and constant. It is what is before our eyes, contrasting and opposing us. We could just remember Ponty’s famous glossing from the Visible and the Invisible that “I have faith in what is perceived”, thus, starting with Merleau-Ponty late phenomenological ontology, we could also discuss the notion of perceptual faith in the world. Alloa’s book also provides us with certain hints concerning how we should read Merleau-Ponty’s oeuvre, thus the author suggests, following Ponty’s reading of Eugen Fink, an author also present in the Phenomenology of Perception, that wonder is precisely the starting point of philosophy, at which we can arrive by loosening our intentional threads which bind us to the world. Therefore, the experience of philosophical thinking would be an utterly strange experience. This strange experience shakes the foundations of our familiarity with the world, introducing us into the philosophical realm per se. The author emphasizes that the notion of transparency is not found in any glossary pertaining to the key concepts of Merleau-Ponty, whereas for Alloa, it is precisely transparency which can be called the leitmotif of Ponty’s work. Therefore, we could discuss transparency in relation to ourselves, with the world and with others. Even though the current exegesis identifies several stages of Ponty’s work, Alloa argues for the continuity of the former’s oeuvre, suggesting that it is precisely perception which provides the unitary aspect of Ponty’s corpus.